Cardiorespiratory Fitness and Body Composition of Soccer Referees; Do These Correlate With Proper Performance? - Mazaheri, Reza (Asian J Sports Med, 2016)
BACKGROUND: The elite-level referee is exposed to similar physical demands to those placed on a midfield soccer player. They have an important responsibility to implement the rules of the game. So, good health and performance of soccer referees have a great importance. OBJECTIVES: The purpose of this study was to assess the cardiorespiratory fitness and body composition of all 78 soccer referees officiating at the Iranian Premier League and determine the correlation between these parameters and performance. PATIENTS AND METHODS: In a cross-sectional study, all referees selected for the competitions were enrolled. Participants underwent exercise stress test, pulmonary function test and body composition assessment. Then the weekly scores of each referee, assessed by qualified supervisors of national federation were obtained using the FIFA standard form throughout the season (34 weeks) and registered. RESULTS: Among 78 participants (including 32 center and 46 side referees), mean and standard deviation of age, body mass index, percent of body fat, VO(2max) and performance scores were 37 ± 3.8, 23.6 ± 2.1, 20.7 ± 3.9, 59.9 ± 7.1 and 85.8 ± 0.25, respectively. No significant correlation between referees’ mean score and selected parameters were found. CONCLUSIONS: It seems that the acquired scores of top-class referees may be influenced by multiple factors other than the laboratory findings of cardiopulmonary fitness and body composition.